2006
DOI: 10.2460/javma.229.5.700
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of DNA of Mycoplasma haemofelis, ‘Candidatus Mycoplasma haemominutum,’ Anaplasma phagocytophilum, and species of Bartonella, Neorickettsia, and Ehrlichia in cats used as blood donors in the United States

Abstract: When community-source cats, cats allowed outdoors, or cats exposed to fleas are to be used as blood donors, they should be regularly assessed for infection with M haemofelis, 'Candidatus M haemominutum,' and Bartonella spp, and flea-control treatment should be regularly provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 44 publications
3
29
1
4
Order By: Relevance
“…(hemoplasmas, formerly classified as Haemobartonella and Eperythrozoon spp.) (4,12,28,29) appear to have coevolved with animals, including dogs, cats, humans, alpacas, capybaras, and sea lions (1,10,13,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The development of molecular assays, which target primarily the 16S rRNA gene of these microbes, has resulted in the more recent recognition of several novel animal hemoplasmas (5,12,37,41).…”
Section: Discussionmentioning
confidence: 99%
“…(hemoplasmas, formerly classified as Haemobartonella and Eperythrozoon spp.) (4,12,28,29) appear to have coevolved with animals, including dogs, cats, humans, alpacas, capybaras, and sea lions (1,10,13,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The development of molecular assays, which target primarily the 16S rRNA gene of these microbes, has resulted in the more recent recognition of several novel animal hemoplasmas (5,12,37,41).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no treatment that effectively clears the microorganisms from an infected host. Chronic infection is well recognized and even in pet cats showing no clinical signs, the prevalence of M. haemofelis infection may be as high as 4% [8]. While transmission of M. haemofelis from an infected cat to a human host has been reported [9], it appears to be a rare event and likely requires immune suppression ([10], Santos AP, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…The individual CMhm and CMt prevalences were similar to previous Brazilian studies Macieira et al, 2008;Miceli et al, 2013;Santis et al, 2014;Santos et al, 2009), however the Mhf prevalence was higher than those previously reported in RS , MA and MT (Miceli et al, 2013). As would be expected, the individual prevalence figures found in our study were lower than those in international studies where only cats attending veterinary practitioners (Jenkins et al, 2013;Lobetti and Lappin, 2012;Spada et al, 2014;Sykes et al, 2007) or cats with a clinical suspicion of haemoplasmosis (Jenkins et al, 2013;Lobetti and Lappin, 2012;Spada et al, 2014;Sykes et al, 2007) were sampled; but higher than those found in clinically normal cats used as blood donors (Hackett et al, 2006). These differences in prevalence may reflect variations in the groups of cats studied and the risk factors for haemoplasma infection.…”
Section: Discussionsupporting
confidence: 84%
“…Conforme esperado, as prevalências encontradas neste estudo foram menores do que aquelas encontradas em estudos internacionais que amostraram gatos pacientes de clinicas veterinárias ou com suspeita de hemoplasmose (Jenkins et al, 2013;Lobetti e Lappin, 2012;Spada et al, 2014;Sykes et al, 2007); mas as prevalências do presente estudo foram maiores do que aquelas encontradas em gatos clinicamente saudáveis usados como doadores de sangue (Hackett et al, 2006).…”
Section: As Prevalências Individuais De Cmhm E Cmt Foram Similares Aqunclassified